Revision of the genus Macrostomus Wiedemann (Diptera: Empididae: Empidinae). I. The ferrugineus species-group - Rafael, José Albertino; Cumming, Jeffrey M. (Zootaxa, 2009)
All species of Macrostomus Wiedemann allied with the type-species, Macrostomus ferrugineus (Fabricius), are treated in the ferrugineus species-group. Three currently recognized species and six new species are included, namely M. fuscithorax, n. sp. from Brazil (Amazonas state), M. fusciventris, n. sp. from Brazil (Amazonas and Acre states), M. melanothorax, n. sp. from Peru and Brazil (Amazonas state), M. ferrugineus (Fabricius), M. longipennis, n. sp. from Brazil (Amazonas state), M. flavus, n. sp. from Brazil (Roraima and Amazonas states), M. furcatus, n. sp. from Brazil (Amazonas and Acre states), M. fulvithorax (Curran) and M. occidentalis Rafael & Cumming. A key to species is presented.